Constraints of Parametrically Defined Guide Vanes for a High-Head Francis Turbine - Stojkovski, Filip; Lazarevikj, Marija; Markov, Zoran; Iliev, Igor; Dahlhaug, Ole Gunnar (MDPI AG, 2021)
This paper is focused on the guide vane cascade as one of the most crucial stationary sub-systems of the hydraulic turbine, which needs to provide efficient inflow hydraulic conditions to the runner. The guide vanes direct the flow from the spiral casing and the stay vanes towards the runner, regulating the desired discharge. A parametric design tool with normalized geometrical constraints was created in MATLAB, suitable for generating guide vane cascade geometries for Francis turbines. The goal is to determine the limits of these constraints, which will lead to future faster prediction of initial guide vane configurations in the turbine optimal operating region. Several geometries are developed using preliminary design data of the turbine and are investigated using CFD simulations close to the best efficiency point (BEP) of the turbine. This research is part of the Horizon-2020—HydroFlex project led by the Norwegian University of Science and Technology (NTNU), focusing on the development of a flexible hydropower generation.